THE SIGNIFICANCE OF LEGAL PRAGMATISM AND ECONOMIC ANALYSIS OF THE LAW FOR THE THEORY OF ADJUDICATION IN THE CONDITIONS OF SOCIAL LIFE - Ганна Коваленко (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія)
The views and ideas of thinkers and actors representing the direction of legal pragmatism and economic analysis of law, whose ideas had the greatest influence on the world philosophical and legal thought and the formation of the philosophical and legal views of judges, are considered. The interaction between the directions of legal pragmatism, economic analysis of law and the formation of judicial philosophy is shown. The highlighted role and significance of legal pragmatism and economic analysis of law for the development of the philosophy of justice, which should be in constant contact with current events and problems, thanks to which it would ensure its leading role in the development of legal theory and practice, through the influence on modern legal thought, in conditions of modern society.